Penerapan Model Matematika pada Kinetika Reaksi Oksidasi Fero Sulfat Menjadi Feri Sulfat dengan Katalis Kupri Sulfat - Neneng Purnamawat; Leo Adhar Effendi (UIN Sultan Syarif Kasim Riau, 2016)
Oxidation of ferrous sulphate to ferric sulphate was conducted in an agitated reactor using cuprisulphate as catalyst. This experiment was performed at ferrous sulphate initial concentration of 0.4 N,reaction temperature of 40-90 C, agitator speed of 220-400 rpm, volumetric rate of gas of 31.94-61.56mL/s. Mass transfer coefficient and reaction rate constant were calculated by using Runge-Kutta andHooke-Jeeves method.Based on the experimentally result, the value of maximum conversion obtained was 30.71% atreaction temperature of 70 C, agitator speed of 290 rpm, and volumetric rate of gas of 40.26 mL/s.Evaluation of mass transfer coefficient and reaction rate constant revealed that the step of controlling theoverall process is chemical reaction.